Resistência biológica da madeira tratada de Eucalyptus grandis e Eucalyptus cloeziana em ensaios de laboratório e campo - Vivian, Magnos Alan (2011)
The Wood, because of its organic origin, depending on environmental conditions that is exposed can be damaged by biological agents. In view of this becomes very important that the same pass for any preservative treatment, in order to increase its lifespan. This study aimed to evaluate the biological resistance of treated wood of Eucalyptus grandis and Eucalyptus cloeziana under the action biodeterioration organisms in laboratory tests and field, comparing the parameters of wood treated with those obtained for untreated wood. For this purpose, used trees of E. grandis and E. cloeziana, both with 16 years of age, belonging to FLOSUL Timber Company. In this, the logs were deployed into planks with dimensions of 2.2 x 9.0 x 200.0 cm, which were subjected to an air drying until a moisture content of 12 to 15%, to then make up the preservative treatment autoclave with chromate copper arsenate (CCA). Then these boards were sent to the Laboratory of Forest Products UFSM for making the specimens for evaluation of physical parameters as density and equilibrium moisture, quality of treatment as penetration and retention, and efficiency, with tests rotting in the laboratory and field. Based on the results, the CCA preservative treatment under pressure to the woods E. grandis and E. cloeziana with 16 years, showed no significant effect on the specific mass, but in the case of equilibrium moisture content was significant increase for both species. Regarding the quality of preservative treatment, the wood of E. grandis showed penetration and vascular distribution and the E. cloeziana partial irregular, retention was unsatisfactory in both species. The preservative treatment were effective in reducing the biological degradation of wood of two species, both in the test laboratory and field. Thus, comparing the results obtained in tests laboratory and field, the wood of E. cloeziana treated under conditions similar to this study has greater ability to be used under conditions adverse, such as decks, or in contact with the ground.